Русские суеверия: [Энциклопед. словарь] / Марина Власова - Власова Марина Никитична (Азбука, 2000)
Экземпляры: КХ (20011015) / Инвентарный номер: 1042010 / Цена: / Сис.шифр: 86.2 / Авт.знак: В 58 / ГРНТИ: 21 / ББК: 86.212.03